Biodegradable Films from Phytosynthesized TiO2 Nanoparticles and Nanofungal Chitosan as Probable Nanofertilizers - Mohamed E. EL-Hefnawy (International Journal of Polymer Science)
Titanium dioxide nanoparticles (TiO2-NPs) have great importance for plant nutrition and growth, at little concentrations. The bioactive polymer chitosan and its NPs provide outstanding characteristics for capping and enhancements of nanometals. The phytosynthesis of TiO2-NPswas promisingly achieved using an extract of pomegranate rind, whereas the fungal chitosan (FCt) was produced from Aspergillus brasiliensis biomass and was transformed to nanoform. The phytosynthesis of TiO2-NPs generated homogenous spherical particles with 13 to 64 nm range and 37 nm mean size. The extracted FCt had 92% deacetylation degree and a molecular weight of 28,400 Da. The infrared spectral analysis of TiO2-NPs, FCt-NPs, and their nanocomposite indicated their functional groups and biochemical interactions. The released amounts of TiO2-NPs from their nanocomposite with FCt–NPs were 31% and 50% after the first and third hour, respectively. The nanocomposite film had a faster hydrodegradability rate which resulted from TiO2-NP addition. Therefore, the fabricated nanocomposite from FCt/TiO2-NPs could have elevated potentiality for application as liquid spray for foliar feeding or as powder for soil amendment.